2013
DOI: 10.1097/won.0b013e318283bcd8
|View full text |Cite
|
Sign up to set email alerts
|

Does Incorporation of a Clinical Support Template in the Electronic Medical Record Improve Capture of Wound Care Data in a Cohort of Veterans With Diabetic Foot Ulcers?

Abstract: Purpose The purpose of this cohort study was to evaluate the effect of a 1 year intervention of an electronic medical record wound care template on the completeness of wound care documentation and medical coding compared to a similar time interval for the fiscal year preceding the intervention. Methods From October 1, 2006 to September 30, 2007, a “good wound care” intervention was implemented at a rural VA facility to prevent amputations in veterans with diabetes and foot ulcers. The study protocol included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Previous studies have already shown that notes generated from templates are more likely to be associated with greater quality of care [29][30][31][32]. This is consistent with initiatives in quality improvement, where use of structured lists and reminders lead to more consistent and better care [33][34][35][36].…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have already shown that notes generated from templates are more likely to be associated with greater quality of care [29][30][31][32]. This is consistent with initiatives in quality improvement, where use of structured lists and reminders lead to more consistent and better care [33][34][35][36].…”
Section: Discussionsupporting
confidence: 74%
“…We chose 30 days because among veterans with healed visits close to the last treatment visit, many occurred around 30 days apart. Finally, during the study period, the Walla Walla Veterans Administration Medical Center (VAMC), which serves a largely rural area, was conducting an intervention to improve wound care and therefore may have provided different wound care during the study . Our third sensitivity analysis excluded veterans who received care at the Walla Walla VAMC (n = 19; all rural) to determine whether this concurrent intervention affected the results of this study.…”
Section: Methodsmentioning
confidence: 99%
“…A new concept to provide the advantages of a multidisciplinary team while overcoming some of the logistical problems is the use of a clinical pathway (preferably accompanied by electronic order-sets). 143 Clinical pathways may uncover improper diagnostic or therapeutic approaches, or bottlenecks in providing optimal care. Order-sets provide a powerful tool to implement 'bundles' (multiple simultaneous interventions) and to encourage and facilitate optimal and evidence-based care.…”
Section: Clinical Pathways Guidelines and Bundle Interventionsmentioning
confidence: 99%